CUERPOS, CUERNOS, AND ESPADAS CEÑIDAS: SEDIMENTING GENDER THROUGH VIOLENCE IN LA MONJA ALFÉREZ - Spragins, Elizabeth (ConSecuencias, 2019)
This article considers how the violently generated corpses left in Catalina de Erauso’s wake form part of a convincing performance of gender and an essential aspect of Erauso’s narrative persona. In Vida y sucesos de la monja alférez, Erauso establishes a predictable cycle of violence that inscribes Erauso within masculine military culture and strews numerous corpses by the wayside. Through the accumulated evidence of these violently created bodies, Erauso builds the foundations of the rhetorical appearance of male-coded credibility. Erauso joins other male soldiers in a social fraternity of textual credibility by demarcating violence within a gendered frame of embodied activity. These soldiers act as compurgatory witnesses that attest to Erauso’s narrative credibility. Erauso reinforces the validity of their narrative by means of certain dead bodies in order to persuade the reader of the story’s truthfulness on an emotional as well as an evidentiary basis. Resumen El artículo considera cómo los cuerpos muertos que produce Catalina de Erauso de modo violente forman parte de una performance convincente del género y un aspecto esencial de su personalidad narrativa. En Vida y sucesos de la monja alférez Erauso establece un ciclo predecible que al repetirse le inscribe dentro de una cultura masculina y militar mientras cadáveres numerosos siguen sus pasos. Al delimitar su violencia dentro de este marco genérico de actividad corpórea, se une con otros soldados varoniles a una fraternidad social de credibilidad textual. Estos soldados luego sirven como testigos compurgatorios que atestiguan a la credibilidad narrativa de Erauso. Erauso fortalece las fundaciones la validez de su narrativa mediante ciertos cuerpos muertos para persuadir al lector de la veracidad de su historia a un nivel tanto emocional como probatorio.